GENDER EDUCATION IN AN ORPHANAGE - Shnaider, Janat; Shnaider, Yelizaveta; Shnaider, Fatima; Zhaparova, Baglan; Akhmuldinova, A. (Pedagogy and Psychology, 2022)
The article substantiates the theoretical aspects of the gender education of orphans in an orphanage. The article presents also an analysis of research on the problem of gender education in orphanages. The authors studied the psychological and pedagogical literature on the gender education of orphans, determined the scientific significance of the study of gender education in an orphanage, substantiated the starting positions, the theoretical provisions of gender education, and the essence of gender education of orphans in an orphanage. The authors also specified the criteria, levels, and diagnostic tools for gender education of orphans in orphanages, identified the methodology of gender education in orphanages and criteria for assessing the formation of gender education of orphans in orphanages, and diagnostic methods. The base of the study was Kenzhekol family-type children's village. The study results are recommended for practical use in orphanages in the process of gender education of orphans in orphanages.